2003
DOI: 10.2807/esm.08.02.00398-en
|View full text |Cite
|
Sign up to set email alerts
|

Explosive increase of Salmonella Java in poultry in the Netherlands: Consequences for public health

Abstract: In the Netherlands Salmonella Paratyphi B variant Java increased in poultry from less than 2% of all isolates before 1996 to 60% in 2002. Despite exposure to contaminated meat is high, human patients with Java infection are rare (0.3% of all isolates). However, 50% of the human isolates showed PFGE profiles identical to the poultry clone. Resistance to flumequin in S. Java increased from 3% between 1996-2000 to 19% in 2001, and 39% in 2002, while that of other serotypes in poultry remained at about 7%. S. Java… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Another notable finding was the emergence of multidrugresistant Salmonella serovar Paratyphi B variation Java strains in chickens. From 1996, 73.2% of these isolates were resistant to more than one antimicrobial drug, with resistance to ampicillin, trimethoprim-sulfamethoxazole, furazolidone, and flumequine predominating (20). This serovar emerged in The Netherlands in 1996, and its prevalence has since increased, being the predominant serotype found in chickens and chicken products in 2001 (30 and 43% of all Salmonella isolates, respectively), replacing Salmonella serovar Enteritidis (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Another notable finding was the emergence of multidrugresistant Salmonella serovar Paratyphi B variation Java strains in chickens. From 1996, 73.2% of these isolates were resistant to more than one antimicrobial drug, with resistance to ampicillin, trimethoprim-sulfamethoxazole, furazolidone, and flumequine predominating (20). This serovar emerged in The Netherlands in 1996, and its prevalence has since increased, being the predominant serotype found in chickens and chicken products in 2001 (30 and 43% of all Salmonella isolates, respectively), replacing Salmonella serovar Enteritidis (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…S. Paratyphi B variant Java (76.4%) and S. Heildelberg (22.7%) were the most prevalent serovars isolated from broiler farms in two distinct regions (Cundinamarca and Santander) of Colombia (Donado-Godoy et al, 2012), thus, this serovar might be distributed in broiler farms across the country and its potential association with natural outbreaks of paratyphoid disease reported by the National Institute of Health (INS, 2015), is worthy of investigation. S. Paratyphi B var Java has been isolated from poultry from Netherlands (Van Pelt et al, 2003) and Germany (Dorn et al, 2001), from chicken viscera at two slaughter plants in the state of Zulia, Venezuela (Boscan et al, 2005), from chicken in Belgium (De Jong et al, 2014), and from breeders and broiler farms in Bangladesh (Barua et al, 2013). In Bangladesh, it was also isolated from blood of patients with clinically diagnosed enteric fever at similar proportions to S. Typhi but with higher resistance rates (Afroz et al, 2014), highlighting an increased risk upon its eventual transmission to human.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in Eurosurveillance show that in the Netherlands the proportion of Salmonella isolates in poultry accounted for by S. Java increased from less than 2 % prior to 1996 to 60 % in 2002. Despite likely exposure through the food chain, cases of S. Java infection in humans remain rare in the Netherlands (0.3 % of all Salmonella infections), although molecular typing has shown that 50 % of human isolates are identical to the poultry clone (van Pelt et al, 2003). The antimicrobial resistance monitoring report for the Netherlands for 2009 (MARAN, 2009) records that, of all ESBL-producing isolates, 22 (67 %) belonged to S. Java derived either from poultry or from an unspecified source.…”
Section: Resistance Levels In S Kentucky From Poultrymentioning
confidence: 99%